Teoretycznoprawne aspekty operacjonalizacji ochrony praw człowieka w państwie z perspektywy globalnego systemu prawa (Zarys problematyki) - Liżewski, Bartosz (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2015)
The article is devoted to the presentation of the outline of the concept of operationalization of human rights taking place in the states involved in the system of international protection of those rights. The concept of operationalization of protection is a collective term for a series of processes that lead to the establishment of legal provisions protecting human rights, and to transfer this abstract construct to specific societies. It includes both the decision-making processes of extralegal (uprising idea, its conceptualization, social issues and change the perception of axiology of society, cultural aspects) and legal (lawmaking and law application processes in the aspect of human rights and the impact of international institutions on them) character. The essence of the process of operationalization is providing effective protection of human rights in a state. The concept is set primarily on the consequences of membership of Poland in the system of the Council of Europe.
Theoretical Aspects of Operationalization of Protection of Human Rights in a State From the Perspective of Global System of Law (An Outline)
Keywords: human rights; operationalisation of human rights protection; value; legal order; decision-making process; controlling mechanism